Identifikasi Faktor Bahaya pada CV X Catering Kota Malang Menggunakan Metode HIRADC (Hazard Identification, Risk Assessment and Risk Control) - Permatasari, Adelia; Sari, Cindy Puspita; Barlian, Salwa Isna; Agustina, Sevia; Adisti, Sefina Febri; Ardiansya, Reynardi Wahyu; Sulistyorini, Anita (Universitas Negeri Malang, 2024)
CV X Catering in Malang City is one of the well-known caterers that caters to various events, such as weddings, birthdays, and other events in large numbers. However, like other industries, the catering industry also has potential hazards to the health and safety of workers, consumers, and other parties involved. CV X Catering in Malang City has experienced workplace accidents. This study aims to identify hazard factors at CV X Catering in Malang City using the HIRADC (Hazard Identification, Risk Assessment and Risk Control) method. This research was conducted using field observation descriptive, interviews with workers, and document analysis. The results showed that there were still high risks and residual risks. Thus, it can be concluded that there needs to be control efforts made for workers at CV X Catering. Technical control efforts include providing personal protective equipment (PPE), improving ventilation, and installing warning signs. Administrative controls provide occupational safety and health (OHS) training, create safe work procedures, and conduct periodic health checks. Personal protective equipment controls increase workers' awareness of OHS hazards and encourage them to use PPE and follow safe work procedures